Being Mad in Early Modern England - Dimitrijevic, Aleksandar (Frontiers in Psychology, 2015)
It has become almost a rule that the birth of scientific psychiatry and what we today term clinical psychology took place in the short period between the last decade of the XVIII century and the 1820s. Everything that happened before that period – every description, diagnosis, and therapy – has been considered ‘pre-scientific,’ outdated, in a way worthless. In this paper, however, I am providing the argument that, first, the roots of contemporary psychiatry reach at least to England of the early modern period, and that, second, it may still turn out that in the field of mental health care historical continuities are more numerous and persistent than discontinuities. Thus, I briefly review the most important surviving documents about the treatment of mental disorders in England of Elizabethan and Jacobian period, organizing the argument around the well-known markers: diagnostics and aetiology, therapy, organization of the asylum, the public image of the mentally ill…